2007
DOI: 10.1007/s11090-007-9057-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Excited States of Atomic Nitrogen N(2D), N(2P) and N(R) on the Transport Properties of Nitrogen. Part II: Nitrogen Plasma Properties

Abstract: In this paper, the calculated values of the viscosity and thermal conductivity of nitrogen plasma are presented taking into account five (e, N, N + , N 2 and N 2 + ) or eight (e, N( 4 S), N( 2 P), N( 2 D), N(R), N + , N 2 and N 2 + ) species. The calculations are based on the supposition that the temperature dependent probability of occupation of the states is given by the Boltzmann factor. The domain for which the calculations are performed, is for p = 1 and 10 atm in the temperature range from 5,000 K to 15,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…We have shown [74] that it is possible to display the influence of the different species on translational thermal conductivity and viscosity. ).…”
Section: Influence Of the Different Speciesmentioning
confidence: 93%
“…We have shown [74] that it is possible to display the influence of the different species on translational thermal conductivity and viscosity. ).…”
Section: Influence Of the Different Speciesmentioning
confidence: 93%
“…There has been a continued interest in studying the role of electronic excitation in affecting the thermodynamic and transport properties of local thermodynamic equilibrium ͑LTE͒ thermal plasmas. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Researchers in the past ignored the importance of electronically excited states ͑EES͒ on the thermodynamic properties due to some sort of compensation between contributions from their different terms. The role of EES on the thermodynamic and transport properties for hydrogen, nitrogen, and oxygen thermal plasmas has been studied by many authors and their results indicate that EES at high pressures do affect these properties.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of EES on the transport properties has been examined in detail for hydrogen [8][9][10][11][12][13][14][15] and nitrogen plasmas. 6,16,17 The thermodynamic and transport properties at atmospheric pressure for argon, nitrogen, oxygen and argon-hydrogen, nitrogenhydrogen plasma mixtures have been studied at different temperatures by Colombo et al 19,20 without taking into account EES. In order to estimate the effect of EES on argon and argon-hydrogen plasma mixture, electron transport properties for the above plasmas have been evaluated at different pressures and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the relevance of the matter, only few examples attempting the derivation of collision integrals for interactions involving excited species are present in the literature. For air speciesnamely oxygen and nitrogen atoms and ionsthe investigation was focused on the so-called low-lying excited states; that is, states sharing the same electronic configuration of the ground term. Collision integrals have been estimated as the weighted average of different electronic states, considering also the contribution due to inelastic channels that affect the odd-order terms. , The dependence on electronic excitation of colliding partners was actually weak; however, the paper by Eletskii, estimating the charge-exchange contribution in highly excited state interactions, demonstrated that greater effects are expected, increasing the principal quantum number.…”
Section: Introductionmentioning
confidence: 99%